The Organic Food Premium: A Canterbury Tale - Adelina Gschwandtner (University of Kent, School of Economics, 2014)
The present paper attempts to bring further evidence on the behavioural gap for organic food in Britain. The stated preferences are analysed by contingent valuation, while the revealed preferences are estimated by hedonic pricing. A small but significant gap in the premium for organic food between stated and revealed preferences has been found. This gap may suggest a need for price premium intervention. The estimated price elasticity for organic products is on average above one in absolute value suggesting that a pricing policy could be very effective.
Keywords: H29; Q18; Q21; 330; Contingent Valuation; Hedonic Pricing Method; Convergent Validity; Behavioral Gap; Organic Food; Price Premium